BETWEEN CUSTOMARY TRADITION AND ISLAMIC NORMATIVITY IN BUGIS SIDRAP MARRIAGES: REASSESSING THE SYMBOLIC STATUS OF BEPPA MENRE THROUGH ‘URF - Jesika Jesika; Abd. Karim Faiz; Aris Aris; Sunuwati Sunuwati (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2026)
This study aims to analyze the types of beppa menre, their symbolic meanings, and the construction of its perceived “obligation” from the perspective of ‘urf in Bugis customary marriages in Sidenreng Rappang Regency (Sidrap). This research is a qualitative field study conducted in Mattirotasi Village, Watang Pulu District, with data collected through in-depth interviews, observation, and documentation involving customary leaders, religious figures, and families who both practice and omit the tradition. The analysis employs ‘urf theory in Islamic law alongside symbolic interactionism to interpret the philosophical meanings embedded in the tradition. The findings reveal six principal types of beppa menre, nennu-nennu, sikaporo, beppa pute, bolu peca, didoro and dadara’ balanda, each representing values of unity, harmony, purity of intention, togetherness, and resilience in marital life. From the perspective of ‘urf, this practice may be categorized as ‘urf ‘amali and ‘urf khas as it is a living custom within the Bugis community, while its perceived “obligation” is socio-cultural rather than a normative requirement under Islamic law. This study contributes to Islamic legal scholarship by enriching discussions on the relationship between customary practices and Sharia principles in contemporary Muslim marriage traditions.